Facets of Globalization : International and Local Dimensions of Development - Yusuf, Shahid; Evenett, Simon; Wu, Weiping (Washington, DC: World Bank, 2013)
The chapters in this volume underscore the transformative role of globalization and urbanization, and show the interplay between these forces. Trade reform and liberalized foreign investment regimess have contributed to the spatial reallocation of economic activity toward cities, especially those cities that can attract and nurture human capital and strong connections to other markets. Global factors have, therefore, reinforced agglomeration economies in shifting economic clout toward cities, and in so doing they may be exacerbating regional disparities in incomes. The rise of cities is changing political dynamics in developing nations. It is forcing a reappraisal of existing constitutional structures and center-local relations, as well as the important--and perhaps more mundane-- arrangements for funding and organizing investment by subnational entities. At the same time, democratization is reinforcing the pressures for local autonomy. This perspective shifts the debate away from whether or not globalization is undermining the role of the central state and toward one about the appropriate allocation of responsibilities and resources to different layers of government. Strong arguments support the position that municipalities can, with the appropriate resources and political structures to ensure their responsiveness to local needs, make substantial improvements in the well-being of urban residents. Experience suggests that some state functions ought to remain with government.